PG 1115+080: NEW ANALYSIS OF LIGHT CURVES CONFIRMS OLD TIME DELAY RESULTS - Artamonov, B.; Koptelova, E.; Oknyanskij, V.; Shimanovskaya, E. (Одеські астрономічні публікації, 2011)
We analyze all publicly available long-term optical observations of the gravitationally lensed quasar PG1115+080 with the aim of measuring time delays between its four components. In particular, we present analysis of the Maidanak light curves of the PG1115+080 components obtained between 2001 and 2006 (Tsvetkova et al. 2010). We find that the light curves of the 2006 observational season show almost linear trend with some fast variations seen only in the A1 and C components. This can be as due to microlensing or observational errors. These fast variations can decrease statistical significance of the time delay estimates or even produce misleading results. Application of the MCCF technique (Oknyanskij 1993) to photometric data collected in the 2004-2005 seasons gives time delay values tBC = 22±3, tAC = 12±3, and tBA = 10±3 days, which are in agreement with previous results of Schechter et al. (1997) and Barkana (1997) reported for the 1995-1996 light curves analyzed using two different statistical methods. The ratio tAC/tBA between our intermediate delays is about 1.2 that is close to the value reported by Barkana ( ∼1.13) and predicted by lens models (∼1.4) unlike the Schechter's and Vakulik's (2009) values (∼ 0.7 and ∼2.7).